Commodity Mutual Fund Performance in Emerging Markets : The Case of India - Agarwal, Sonali; Raychaudhuri, P. S. (Indian Journal of Research in Capital Markets, 2017)
Diverse events take place every day in our country and abroad, which may have deeper consequences on our economy and investors' perception. A common man, who wants to earn profits by investing in the economy through stock markets, is often left helpless due to the sudden changes in the market behavior. This leads to suspicion and fear in the investors' mind. To avoid suchÂ traps, it becomes imperative to analyze the risks from investments beforehand. Since the common man is incompetent to do so, intermediaries like mutual funds are resorted to. However, the selection of the right asset management company and the right scheme is very important. In this study, 41 mutual funds were taken of which 14 were gold mutual funds, 12 were exchange traded funds, and 15 were energy mutual funds. We studied the performance of mutual funds using different portfolio measurement methods, models, and ratios. Capital asset pricing model was used for most of the interpretations. Various performance related facts were highlighted in this study. In general, it was found that the gold funds performed better than the energy funds and moved in tandem with their benchmark index.